Survey of Inmates of State Correctional Facilities, 1991: (United States) ([Verlag nicht ermittelbar], 1993)
This survey provides nationally representative data on persons held in state prisons and is similar to surveys conducted in 1974 (ICPSR 7811), 1979 (ICPSR 7856), and 1986 (ICPSR 8711). The survey was designed to provide information on individual characteristics of prison inmates, their current offenses and sentences, characteristics of victims, criminal histories, prior drug and alcohol use and treatment, gun possession and use, gang membership, family background, and prison activities, programs, and services.